Քրդերի սոցիալ–քաղաքական վիճակը Թուրքիայում (1920-30թթ.) - Մանուկյան, Տաթևիկ («Զանգակ - 97»)
The events of 1920-1930's are the most remarkable in Kurd's history. For the first time during the hisiory of Kurds after the seal of Severe's Convention it became touchable for the Kurds the perspective of the creation of independent Kurdistan. However because of Kurds own mistakes and with the influence of externa! factors the Kurdish question in Lozano's (Lasagna's) conference stayed out of the day program of International Diplomacy. We would like to accent also that due to Turkey's carried out double standard effective policy Turkey succeeded in even though temporally solving the Kurdish problem.
Keywords: Պատմություն; Քաղաքականություն